Proceedings of the 18th International Conference on Evaluation and Assessment in Software Engineering 2014
DOI: 10.1145/2601248.2601270
|View full text |Cite
|
Sign up to set email alerts
|

Tools to support systematic reviews in software engineering

Abstract: BackgroundThe labour intensive and error prone nature of the systematic review process has led to the development and use of a range of tools to provide automated support.Aim The aim of this research is to evaluate a set of candidate tools that provide support for the overall systematic review process.Method A feature analysis is performed to compare and evaluate four candidate tools. ResultsEach of the candidates has some strengths and some weaknesses. SLuRp has the highest overall score and SLRTOOL has the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 22 publications
0
50
0
15
Order By: Relevance
“…In [118], some of these tools are addressed. Two of these tools are StArt (State of the Art through Systematic Review) [55] and SLR-Tool [59].…”
Section: Discussionmentioning
confidence: 99%
“…In [118], some of these tools are addressed. Two of these tools are StArt (State of the Art through Systematic Review) [55] and SLR-Tool [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, the tools have not been properly evaluated and the identified primary studies presented only some case studies or small experiments to exemplify the use of a tool or its effectiveness. Four tools (StArtState of the Art through Systematic Review [5], SLuRp, SLRTool, and SLRTool) support the whole SR process and they are evaluated in [9]. The authors used feature analysis to check the SR activities that each tool supports.…”
Section: Background and Related Workmentioning
confidence: 99%
“…A more recent work that presented a tool to support empirical studies was the Marshall and Brereton work [54]. They showed a research of some tools to support systematic mapping studies, and they concluded that there are a variety of tools are available to support the SLR process although many are in the early stages of development and usage.…”
Section: Related Workmentioning
confidence: 99%